Footprints at the window - Naylor, Phyllis Reynolds (New York : Atheneum, 1981)
Beset by an enemy from within, Dan searches for the gypsies he once knew in York and is led inexplicably into a calamity involving the Black Death in a hostile country among frightened and superstitious people.
5.7
5-8
5-8
School Library Journal
Book Links (A.L.A.)
Booklist
Keywords: Space and time -- Fiction; Space and time -- Fiction; England -- Fiction; England -- Fiction